Exploring predictors of the five-time sit-to-stand test based on cross-sectional findings from the Swedish National Study on Aging and Care (SNAC) - Joakim Niklasson; Cecilia Fagerström; Sofia Backåberg; Patrick Bergman; Terese Lindberg (BMC Geriatrics)
Abstract Background As we age, staying physically active and reducing sedentary behavior becomes crucial. To understand how to achieve this, factors related to daily physical function such as five-time sit-to-stand (STS) time should be explored. This study aimed to investigate the associations between STS time, self-rated physical activity, physical function, health-related quality of life, physical and mental health in community-dwelling older adults aged ≥ 60 years. Method Cross-sectional design with self-reported and objectively measured data from adults aged ≥ 60 years (n = 819), acquired from the Swedish National Study on Aging and Care. Data was analyzed through multiple linear regression. Results The model (R2 = 0.268) showed that STS time was predicted by grip strength (β’ = -0.204, p < 0.05), age (β’ = 0.202, p < 0.05), health-related quality of life (β’ = -0.192, p < 0.05), having fallen within the preceding twelve months (β’ = -0.127, p < 0.05), physical activities of perceived light to moderate intensity (β’ = -0.121, p < 0.05), one-leg stand (β’ = -0.099, p < 0.05), and education level (β’ = -0.092, p < 0.05). For STS time, health-related quality of life (β = -0.354, confidence interval [CI] (-0.509)–(-0.199)), having fallen within the preceding twelve months (β = -0.222, CI (-0.365)–(-0.078)), and physical activities of perceived light to moderate intensity (β = -0.166, CI (-0.278)–(-0.053)) were the most prominent predictors. Conclusion The model highlights the importance of grip strength and health-related quality of life in predicting STS time in older adults. Clinicians can use these insights to develop interventions that maintain physical function by regularly assessing and monitoring these factors. Future research should explore the relationship between fall history, faster STS time, and the impact of grip strength and health-related quality of life on sedentary behavior among older adults.